THz-photomixer based on quasi-ballistic transport - Döhler, Gottfried; Renner, Frank; Klar, Oliver; Eckardt, Martin; Schwanhäußer, Axel; Malzer, Stefan; Driscoll, Dan; Hanson, Micah; Gossard, Art; Loata, gabriel; Löffler, Torsten; Roskos, Hartmut (Semiconductor Science and Technology, 2005)
We report on a novel concept for THz photomixers with high conversion efficiency up to several THz. In contrast to the conventional pin photomixer we can overcome the trade-off between either optimizing transit-time or RC-roll-off. Using quasi-ballistic transport in nano-pin-diodes the transport path can be optimized regarding both path length and transit time. Independently, the capacitance can be kept small by using a sufficiently large number of optimized nano-pin-diodes in series. The concept is presented in detail and first experimental results are reported which corroborate our theoretical expectations. © 2005 IOP Publishing Ltd.